Superfícies invariantes com curvatura média constante no grupo de Heisenberg - Souza, David Carneiro de (2009)
In this paper we study the invariant surfaces with constant mean curvature in the Heisenberg group.This group will generated by a combination of four rigid movements, which define the movements of rotation and translation. The group of Heisenberg is formed by the upper triangular matrices with main diagonal and only the number 1 and as a contained in M3(R). We will see that this group with the operation of multiplication of matrices is a Lie group. We two theorems study the classification of these areas,which will be generated by rotations and translations in the group of elements Heisenberg.